Assessing the Role of Career Development, Motivation, and Job Satisfaction in Enhancing Nurse Performance at Pertamina Hospital - Dewi Komalasari; Hartanto Halim; Eman Sulaiman (International Journal of Management, Economic, Business and Accounting, 2025)
Purpose of the study — This study aims to obtain qualified nurses by analyzing the influence of career development, motivation, and job satisfaction on nurses’ performance at Pertamina Cirebon Hospital. Research method—The study employed a quantitative method. Data were processed using IBM SPSS Statistic 25, and the sample consisted of 64 nurses, determined through the Slovin formula. Result— Partial test results indicate that career development (t = 2.214 > 1.670; sig. 0.031 < 0.05) and work motivation (t = 3.993 > 1.670; sig. 0.000 < 0.05) have a positive and significant effect on nurses’ performance. Job satisfaction (t = 1.733 > 1.670; sig. 0.088 < 0.05) also shows a positive and significant influence. Simultaneous testing (F = 41.201 > 2.75; sig. 0.000 < 0.05) reveals that career development, motivation, and job satisfaction collectively have a positive and significant impact on nurses’ performance. Conclusion— Work motivation is the most dominant factor affecting nurses’ performance, while job satisfaction requires more attention. Pertamina Cirebon Hospital needs to improve job satisfaction effectively to further enhance nurses’ performance.